THE EFFECT OF COLLABORATIVE LEARNING MODEL ON STUDENT’S WRITING ANNOUNCEMENT ABILITY AT X GRADE OF SMA N 1 ANGKOLA BARAT.” - kamisah S.Pd M.Pd (JURNAL LINER (Language Intelligence and Educational Research), 2020)
The aim of this research are to know: 1) The extent of the application of collaborative learning model on students’ writing announcement ability, 2) The extent of the students’ writing announcement ability before and after of collaborative learning model 3) Whether there is any significant effect of collaborative learning model on students’ writing announcement ability at X grade of SMA N 1 Angkola Barat. This research uses experimental method with the pre-experimental design by using one-group pre test and post test design. The population of this research is all of the X grade students’ of SMA N 1 Angkola Barat which consist of 180 students. Sample were X MIPA 1 which consist of 32 students which taken by cluster sampling. In collecting the data the researchers uses observation sheet and test as an instrument. The result of this research: 1) the application of collaborative learning model is 3.26, it is categorized “Very Good”. 2) The mean score of the students’ writing announcement ability is 57.2 and it is categorized “bad”. Meanwhile, after using collaborative learning model was 78.7, it is categorized “good”. The result of data analysis shows that ttestis higher than ttable(ttest10.28 >ttable2.04). So, the hypothesis is accepted. It means that, 3) there is a significant effect of collaborative learning model on students’ writing announcement ability at the X grade students of SMA N 1 Angkola Barat